IRNSS/NavIC Single-Point Positioning: A Service Area Precision Analysis. Issue 4 (4th July 2017) - Zaminpardaz, Safoora; Teunissen, Peter J. G.; Nadarajah, Nandakumaran
ABSTRACT: The Indian Regional Navigation Satellite System (IRNSS) has recently (as of May 2016) become operational. The system has been developed with the objective of offering positioning, navigation, and timing (PNT) to users in its two service areas, covering the Indian landmass and the Indian Ocean, respectively. It is the goal of this contribution to provide further insight into the full-constellation L5 pseudorange single-point positioning (SPP) capabilities of the system. A detailed dilution of precision (DOP) analysis of its two service areas, including the identification, in location and time, of poor receiver-satellite geometries is provided. It is hereby demonstrated how the impact of some of these poor receiver-satellite geometries can be mitigated by means of height-constraining. An overview and analysis of the SPP precision is also provided including easy-to-use representative day-averaged values for a grid of locations covering the two service areas.